2009
DOI: 10.1055/s-0028-1109733
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Expert Consultation via a Teleradiology Platform – Influence on Therapeutic Decision-Making and Patient Referral Rates to an Academic Tertiary Care Center

Abstract: In addition to teleradiological reporting as a nighthawking or a regular service, teleradiological communication can be used for interdisciplinary expert consultation. We intended to evaluate an interdisciplinary consultation system based on a teleradiology platform with regard to its impact on therapeutic decision-making, directed patient referrals to an academic tertiary care center and the economic benefit for the hospital providing the service. Therefore, consultations from five secondary care centers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In this study, we evaluated the added value of a video-conferenced MDT between one oncology centre and its preferred partner. In line with other studies,30 31 this study showed that, in addition to a quantitative result (number of recommendations), it is important to reflect on the situation through an interview process (qualitative results) before starting to implement improvements. The interviews showed that specialists from both centre and partner support the idea of sustainable collaboration, but they do not support the view implicit in the DHCI requirement that the centre should act as means of quality control for the partner 32.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we evaluated the added value of a video-conferenced MDT between one oncology centre and its preferred partner. In line with other studies,30 31 this study showed that, in addition to a quantitative result (number of recommendations), it is important to reflect on the situation through an interview process (qualitative results) before starting to implement improvements. The interviews showed that specialists from both centre and partner support the idea of sustainable collaboration, but they do not support the view implicit in the DHCI requirement that the centre should act as means of quality control for the partner 32.…”
Section: Discussionsupporting
confidence: 84%
“…The most common speciality reporting economic outcomes was paediatrics (n=7) (63)(64)(65)(66)(67)(68)(69) . Simple cost analysis was used by (n=14) (52,(63)(64)(65)(66)(67)(70)(71)(72)(73)(74)(75)(76)(77) studies measuring the cost avoidance, cost saving and added revenue. While (n=15) (27,30,35,58,68,69,(78)(79)(80)(81)(82)(83)(84)(85)(86) studies conducted a cost minimization analysis as a method to assess the economic benefits of telemedicine.…”
Section: Economicmentioning
confidence: 99%
“…For smaller community hospitals, the result was assurance of quality treatment, reducing wasted resources, and unfit treatment plans. 5 Current market conditions and legislation present potential barriers to entry that must be taken into consideration throughout the deployment process. Working knowledge of federal and state-specific legislation and regulatory issues is critical to appropriate delivery of care.…”
Section: Introductionmentioning
confidence: 99%